PERSEPSI KEPALA SEKOLAH TERHADAP PENDAMPINGAN PENGAWAS SEKOLAH DALAM MEWUJUDKAN SEKOLAH RAMAH ANAK DI KABUPATEN KEPULAUAN SELAYAR - Ramlawati Ramlawati; Risnawati Risnawati; Syahrul Syahrul; Suryadi Ishak (Journal Peqguruang: Conference Series, 2025)
If article was written in Indonesian, abstract was written in English and Indonesian. If article was written in English, abstract was written in English only. Abstract should be no longer than 200 words. The body text of abstract is written with Century (8 pt) and justify format, with left indent 10 mm and right indent 10 mm This research aims to analyze the perceptions of school principals regarding the assistance of school supervisors in realizing Child Friendly Schools (SRA) in Selayar Islands Regency. Assistance from school supervisors is considered important to ensure the implementation of policies and practices that support the creation of a safe, comfortable and inclusive learning environment for children. This research used a qualitative approach with descriptive methods, involving 24 school principals as respondents. Data was collected through in-depth interviews, questionnaires and observations, then analyzed using thematic analysis techniques. The research results show that overall, principals' perceptions of school supervisor assistance are at a very positive level (average score 4.27). The dimensions of support and attention (4.47) and communication and collaboration (4.38) were the most appreciated aspects. However, the dimensions of the impact of mentoring (4.14) and increasing understanding and competence (4.15) show quite significant variations in perception, indicating the need for more structured and specific mentoring. Based on these findings, this research recommends increasing the intensity of mentoring, facilitating discussion forums between school principals, and providing more measurable and solution-based feedback. It is hoped that the research results can become a reference for education stakeholders in optimizing the implementation of Child Friendly Schools.